2014
DOI: 10.1260/1369-4332.17.2.197
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Design of Network Arch Bridge Using Global Optimization Algorithm

Abstract: An optimization approach of network arch bridges using a global optimization algorithm EVOP is presented in this paper. The objective is to minimize the cost of superstructure particularly arches and hangers of network arch bridge by optimizing the geometric shape, rise to span ratio, cross section of arch, and the number, arrangement and cross sectional dimensions of hangers. Constraints for design are formulated as per AASHTO, AISC and ACI Specifications. The minimum cost design problem is characterized by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Tey obtained minimal bending moments at the angle values α � 42-55 °. Similar problems were investigated by Islam Ahsan and Ahsan [15,16], and Pipinato [17,18]. Islam Ahsan showed that circular arch network bridges compared to parabolic arch bridges have a lower arch rise and a lesser number of hangers.…”
Section: Introductionmentioning
confidence: 61%
“…Tey obtained minimal bending moments at the angle values α � 42-55 °. Similar problems were investigated by Islam Ahsan and Ahsan [15,16], and Pipinato [17,18]. Islam Ahsan showed that circular arch network bridges compared to parabolic arch bridges have a lower arch rise and a lesser number of hangers.…”
Section: Introductionmentioning
confidence: 61%
“…In ref. [78], another optimized design using a global optimization algorithm (EVOP) was presented. EVOP was interfaced with Ansys to evaluate the structural response of the bridge.…”
Section: Hanger Arrangementmentioning
confidence: 99%
“…erefore, the truss arch design should be optimized by iterating the maximum main tube eccentricity of each truss section to an admissible value range [27,28].…”
Section: Iterative Calculation Of Main Tube Eccentricitymentioning
confidence: 99%